Research status in Halal: A review and bibliometric analysis - Abid Haleem; Mohd Imran Khan; Shahbaz Khan; Abdur Rahman Jami (Modern Supply Chain Research and Applications, 2020)
Purpose - Halal is an emerging business sector and is steadily gaining popularity among scholars and practitioners. The purpose of this paper is to critically evaluate and review the reported literature in the broad area of Halal using bibliometric technique and network analysis tools. Moreover, this paper also proposes future research directions in the field of Halal. Design/methodology/approach - This paper employed a systematic review technique followed by bibliometric analysis to gain insight and to evaluate the research area associated with Halal. Furthermore, data mining techniques are used for analysing the concerned article title, keywords and abstract of 946 research articles obtained through the Scopus database. Finally, network analysis is used to identify significant research clusters. Findings - This study reports top authors contributing to this area, the key sub-research areas and the influential works based on citations and PageRank. We identified from the citation analysis that major influential works of Halal are from the subject area of biological science and related areas. Further, this study reports established and emerging research clusters, which provide future research directions. Research limitations/implications - Scopus database is used to conduct a systematic review and corresponding bibliometric study; the authors might have missed some peer-reviewed studies not reported in Scopus. The selection of keywords for article search may not be accurate for the multi-disciplinary Halal area. Also, the authors have not considered the banking/financial aspects of Halal. The proposed four research clusters may inform potential researcher towards supporting the industry. Originality/value - The novelty of the study is that no published study has reported the bibliometric study and network analysis techniques in the area of Halal.
Keywords: 650; Bibliometric analysis; Halal; Halal supply chain management; Research clusters